2005
DOI: 10.1063/1.2139841
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of a semipolar (101¯3¯) InGaN∕GaN green light emitting diode

Abstract: We demonstrate the growth and fabrication of a semipolar (101¯3¯) InGaN∕GaN green (∼525nm) light emitting diode (LED). The fabricated devices demonstrated a low turn-on voltage of 3.2V and a series resistance of 14.3Ω. Electroluminescence measurements on the semipolar LED yielded a reduced blueshifting of the peak emission wavelength with increasing drive current, compared to a reference commercial c-plane LED. On-wafer measurements yielded an approximately linear increase in output power with drive current, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
152
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 224 publications
(161 citation statements)
references
References 14 publications
4
152
0
1
Order By: Relevance
“…For lower inclination angles ϑ , i.e. for semi-polar orientations, the overlapping depends on a distance of ϑ from its value (about 34 • ) corresponding to [20,21,23,26,27,29,31] the same polarizations in both the quantum well and the barrier (Fig. 6).…”
Section: Designing Of Nitride Leds With Reduced Polarization Effectsmentioning
confidence: 99%
“…For lower inclination angles ϑ , i.e. for semi-polar orientations, the overlapping depends on a distance of ϑ from its value (about 34 • ) corresponding to [20,21,23,26,27,29,31] the same polarizations in both the quantum well and the barrier (Fig. 6).…”
Section: Designing Of Nitride Leds With Reduced Polarization Effectsmentioning
confidence: 99%
“…In particular, the inclined (1-10-3) GaN NRs were formed through the one-sided (10-11)-faceted growth of the interfacial a-GaN layer that was grown on r-facet nanogrooves formed on m-sapphire substrates after nitridation. In our previously published results, growth of inclined (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) GaN NRs was also observed on the c-plane facets of a-GaN nucleation. 23,24 As a result, we found that the a-GaN nucleation layer plays an important role in the growth along different directions of inclined GaN NRs on nitridated m-sapphire substrates.…”
Section: -2mentioning
confidence: 99%
“…Lee et al AIP Advances 6, 045209 (2016) opposite directions with reference to [11][12][13][14][15][16][17][18][19][20] m-sapp . 22 Thus, the layered growth of films purely in the (1-10-3) orientation has resulted in a rough surface and the degradation of crystal quality.…”
Section: -2mentioning
confidence: 99%
See 2 more Smart Citations